2000
DOI: 10.1159/000054605
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Stimulates Mouse Neuropeptide Y-Y<sub>1</sub> Receptor Gene Transcription by Binding to Estrogen Receptor Alpha in Neuroblastoma Cells

Abstract: Several studies have shown that neuropeptide Y (NPY) is involved in the stimulation of gonadotropin hormone releasing hormone (GnRH) and luteinizing hormone (LH) secretion and that these effects are modulated by gonadal steroid feedback. The NPY regulation of GnRH release is probably mediated by the activation of the Y1 receptor subtype. In this study we examined the regulation of the Y1 receptor gene transcription by estrogens in transiently transfected NG108-15 neuroblastoma glioma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
3
11
1
Order By: Relevance
“…3B). Studies in NG-108-15 cells transfected with ERa and/or ERh showed that the presence of ERh attenuates basal as well as ERa-induced Y1R gene promoter activity (32). These findings are consistent with earlier reports that activation of ERh can inhibit ERa-mediated activity in certain cell lines (33).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3B). Studies in NG-108-15 cells transfected with ERa and/or ERh showed that the presence of ERh attenuates basal as well as ERa-induced Y1R gene promoter activity (32). These findings are consistent with earlier reports that activation of ERh can inhibit ERa-mediated activity in certain cell lines (33).…”
Section: Discussionsupporting
confidence: 91%
“…Human genomic cloning studies revealed that three different promoters regulate the Y1R gene in a tissue-specific manner (35). A chimeric plasmid containing mouse Y1R promoter linked to luciferase reporter gene activity was increased 2-fold by estrogen (32) in transfected NG-108-15 cells. In the same study, introducing mutations in both ERE sites abolished the estrogen-induced gene activity (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the predominant ER isoform present in brain areas is the noninducing ER␤ isoform, this is precisely the case. The inability of ER␤ to induce transcription in response to 17␤-estradiol has also been reported in transiently transfected NG108 -15 neuroblastoma glioma cells using a neuropeptide Y-Y1 receptor gene promoter (117). This receptor promoter has two half-site ERE, and estrogen-mediated transcription is strictly dependent on the presence of transfected ER␣.…”
Section: Cross-talk Between the Er␣ And Er␤ Isoformsmentioning
confidence: 71%
“…NPY has been suggested to be involved in the feeding stimulation action of orexins through mediation of Y1 and Y5 receptors [3, 10, 39]. Further, similar to orexin A, icv injection of NPY was either stimulatory [40, 41]or inhibitory [40, 42]to LH secretion depending on the endocrine status of the animals, mediated by either Y1, Y4 and/or Y5 receptors [43, 44, 45, 46], and the NPY/Y1 receptor system has been shown to be activated by estrogen [47]. It is possible then that estrogen potentiates the action of orexin A by activating the NPY/Y1 system.…”
Section: Discussionmentioning
confidence: 99%